Belajar dan Mengenal Huruf Hijaiyyah MenggunakanMetode Iqro’ Pada Anak Usia Dini - Herisyah listiyeni; Dwi hurriyati (JPPMI: Jurnal Pelayanan dan Pemberdayaan Masyarakat Indonesia, 2026)
Children's ability to learn and recognize Hijaiyah letters is very low like a childnot able to recognize Hijaiyah letters, children cannot mention Hijaiyah letters, and the child has not been able to read short verses which are verses that are very important to them. This research is a research that aims to find outwhat are the factors in the decline in interest in the Koran in early childhood .. As for the methodwhich is used in this research is the method of community Iqrothe target is the children who are in the street where the red eyes arein the mangosteen hall, kalidoni subdistrict, palembang. Who is the subject of researchThese are the children who are in the takwah street of the mangosteen alley. thattotaled 10 children consisting of 6 boys and 4 childrengirls. Based on the research that has been done, the results obtainedafter the data analysis was held it can be concluded that learning and getting to knowHijaiyah letters through the iqro method in early childhood can improve reading comprehensionand megaji children with a percentage from 30% to 70%. This means improvement the ability to learn and recognize Hijaiyah letters in early childhood has reached the expected target, with this community service activitywill be more helpful for children and parents to be more concernededucation in the field of Koran to their children, by way of teachingthey teach the Koran at home taught by their respective parentsat home because learning the Koran is very important for their future morning.